Knowledge Management and the Governmental Organisations - Asadi, Rahil; Mihoreanu, Larisa; Radu, Vasilica Georgiana (Journal of Economic Development, Environment and People, 2020)
Abstract. Nowadays, the concept of Knowledge Management is gradually being recognized in governmental establishments which are seeking to deploy their own knowledge management system and make the most of their existing knowledge in policymaking, by creating and maintaining a competitive advantage in the domestic and international environment. For an organisation, the intellectual assets and individual knowledge are as important as the other physical and financial assets. Knowledge is a primary resource featured to provide a competitive advantage to any organization that recognises and incorporates it efficiently in its processes. This article aims to review the value of knowledge management, the pillars by describing its cycle and highlighting its importance for governmental organisations. The obstacles and difficulties of implementing and deploying knowledge management in government organisations with suggested solutions that are also discussed. In conclusion, recommendations for decision makers are presented to enhance the efficiency of the knowledge management implementation and scale up the gain of a lasting competitive advantage within national and international environments.